Resistance towards wiki: implications for designing successful wiki-supported collaborative learning experiences - Yusop, F.D.; Muhammad Abdul Basar, S.M. (Springer Verlag (Germany), 2017)
Wikis are online tools best used to support collaborative learning experiences of students. Not all students, however, are sufficiently comfortable in using wikis; some simply resist using them. Unfortunately, very little research has been devoted to exploring the issue of wiki resistance among higher-education learners. The authors argue that understanding factors contributing to wiki resistance is as important as understanding factors that promote its use, because such understanding supports better comprehension of the limitations of social-media technologies used in instruction. This paper thus presents a qualitative inquiry regarding the issue of resistance to using wikis among full-time undergraduate students. The participants were purposely selected because they evidenced the strongest resistance towards wikis compared to other participants who received wiki-based instruction from the same instructor. In-depth content analyses of 24 students’ written reflections, weekly wiki logs and edit history, three focus-group interviews, and weekly observations of students’ online activities were studied to gain deeper understanding. Two (2) categories of factors emerged from the findings: technical factors (slow Internet connection outside the classroom and user-friendliness aspects of wiki) and individual factors (anxiety in using new technology, mental perceptions, and lack of student commitment towards learning experiences) with the latter representing the strongest resistance factors. Limitations of the study are discussed, and recommendations for helping other instructors in designing successful wiki-supported environment in their own contexts are offered.